Uysal, T., Hamzaoğlu, E., Ertuğrul, K. & Bozkurt M. (2016) A new species of Centaurea (Asteraceae) from Turkey. Phytotaxa 275 (2): 149–158. - Uysal, Tuna; Hamzaoğlu, Ergin; Ertuğrul, Kuddisi; Bozkurt, Meryem (Phytotaxa, 2016)
N/A